Differences in social representations about school of pupils with and without behavior disorders (Studia Doctoralia Psychology and Educational Science, 2012)
The research is based on the premise that social representations are both a form of acknowledging the reality and clues on bow one is interpreting that reality. In this respect, we presume the existence of certain differences between the social representation about school of pupils without any behavior disorders and those with this kind of disorders. Such differences are proved by the current study. The results show that pupils with behavior disorders are likely to associate with school rather negative elements, such as boredom, fatigue, tests, while the social representation of the pupils without behavior disorders is mostly centered on positive elements, such as play, beauty or cleanliness. These findings have implications upon the differentiated psychopedagogical strategy used to work with children with behavior disorders in comparison with those without such disorders.